Developing a Decision Model for Korean Content Productions to Select an Asian Country for Original IP Sourcing - Jaeyoung Park (International Telecommunications Society (ITS), 2024)
The escalating global demand for Asian movies and TV shows indicates a shift away from a Western-centric focus, particularly the United States, with Korean intellectual properties playing a pivotal role. Since the late 1990s, Korean productions have established a regional network within East Asia and, with the advent of digital platforms, achieved a transnational reach. However, investments from global platforms like Netflix, while fostering Korean intellectual properties, often result in these platforms retaining complete content rights, limiting further utilization by local producers. Additionally, there are concerns that platform-driven production may diminish the innovativeness of content by standardizing storytelling and formats. Therefore, Korean content productions need to develop their own transnational network to fully leverage the benefits of transnationalization. Among transnationalization strategies, this paper focuses on transnational inbound innovation as a valid strategy, given that acquiring innovative IP is critical in the content business. To address this, the study proposes a decision model for Korean productions to source original intellectual properties from Asian countries using the Analytic Hierarchy Process (AHP). Focusing on select Asian countries—Indonesia, Thailand, and India—known for significant Korean content consumption and collaboration experience, the study aims to measure the priorities of alternatives and criteria influencing this decision-making process.
Keywords: 330; Transnationalization; innovation management; inbound innovation; Korean content production; Asian original IP; analytic hierarchy process (AHP); multicriteria decision-making